An adaptive feedback methodology for determining information content in stable population studies - H. T. Banks; John E. Banks; R. A. Everett; John D. Stark (Mathematical Biosciences and Engineering)
We develop statistical and mathematical based methodologies for determining (as the experiment progresses) the amount of information required to complete the estimation of stable population parameters with pre-specified levels of confidence. We do this in the context of life table models and data for growth/death for three species of Daphniids as investigated by J. Stark and J. Banks [17]. The ideas developed here also have wide application in the health and social sciences where experimental data are often expensive as well as difficult to obtain.